Power line communication technology based on morphological filtering for machine-to-machine applications. (July 2021) - Pereira, Samuel C.; Casella, Ivan R.S.; Capovilla, Carlos E.; Sguarezi Filho, Alfeu J.; Costa, Fabiano F.
Abstract: This work proposes a communication system based on G3-PLC (G3 - Power Line Communication) technology and a Morphological Filter (MF) for the transmission of analogue Generic Reference Waveforms (GRW) in Machine-to-Machine (M2M) applications (e.g., power control of wind turbines). The presented proposal allows to reduce the system latency without compromising the integrity of the GRW, even in very severe operating conditions, through the use of a MF and the deactivation of the G3-PLC retransmission protocol. Computer simulations were performed considering a very accurate and representative model of the physical layer of the G3-PLC and the communication channel and the results obtained demonstrated the efficiency of the proposed system in recovering the transmitted GRW without the need for retransmissions, reducing considerably the system latency, and making possible real-time M2M communications. Graphical abstract: Highlights: A novel approach to improve reliability and reduce latency of M2M communications. Morphological filtering of analogue signals transmitted by G3-PLC-based M2M systems. System performance simulation analysis based on BER, range and latency. Use of a realistic multipath channel model with background and impulsive noise.